Analysis of marine microbial communities colonizing various metallic materials and rust layers. Issue 4 (21st April 2019) - Zhang, Yimeng; Ma, Yan; Duan, Jizhou; Li, Xiaohong; Wang, Jing; Hou, Baorong
Abstract: High-throughput sequencing was used to visualize microbial biocoenoses on different metallic surfaces and rust layers of highly corroded steels after immersion in coastal marine water for 30 months at Sanya, China. Distinct microbial community compositions were observed on these metallic surfaces. The dominant genus was the copper-tolerant, acid-producing Lactobacillus on copper alloys, the common aerobic surface colonizers Bacillus and Ruegeria on aluminum alloys, and aerobic biofilm-forming Pseudomonas on carbon steel. Most of these are copiotrophic microbes compared to planktonic microbes, which are oligotrophic. Additionally, sulfate-reducing prokaryotes (SRP) were detected in the rust layer, but the dominant genera changed from the outer layer to the inner part. The dominant genera detected in the outer, middle and inner rusts layers were Desulfotomaculum, Desulfonatronum (obligate anaerobe) and Desulfovibiro (electroactive), respectively. Further, the coexistence of methanogens with SRP suggests interspecies interactions.